2021
DOI: 10.1038/s41598-021-03345-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in trabecular meshwork stem cell content in donor eyes with primary open angle glaucoma

Abstract: We previously identified and characterized human trabecular meshwork stem cells (TMSCs) based on high expression of ABCG2/p75 positivity and high nucleus to cytoplasmic ratio. These TMSCs expressing high ABCG2 and p75 were located to the insert region of the human TM. Additionally, we demonstrated an age-related reduction in the TMSC content which was significantly associated with TM cell loss. In continuation, this study was aimed to determine the TMSC content in glaucomatous donor eyes wherein a drastic redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Aging results in a reduction in the number of cells in the outflow system of the normal eye, which is associated with some of the structural changes that occur as we age, such as trabecular thickening and fusion [ 9 , 10 ]. Compared with age-matched controls, patients with POAG have been found to lose a greater number of TM cells as they age [ 11 , 12 ]. Moreover, it has been suggested that the absence of TM cells, followed by their replacement with extracellular matrix (ECM) leads to increased resistance to fluid outflow in these patients, thus triggering an increase in IOP [ 13 ].…”
Section: Introduction: Aging and Glaucoma Are Intimately Linkedmentioning
confidence: 99%
“…Aging results in a reduction in the number of cells in the outflow system of the normal eye, which is associated with some of the structural changes that occur as we age, such as trabecular thickening and fusion [ 9 , 10 ]. Compared with age-matched controls, patients with POAG have been found to lose a greater number of TM cells as they age [ 11 , 12 ]. Moreover, it has been suggested that the absence of TM cells, followed by their replacement with extracellular matrix (ECM) leads to increased resistance to fluid outflow in these patients, thus triggering an increase in IOP [ 13 ].…”
Section: Introduction: Aging and Glaucoma Are Intimately Linkedmentioning
confidence: 99%
“…Aging results in a reduction in the number of cells in the outflow system of the normal eye, which is associated with some of the structural changes that occur as we age, such as trabecular thickening and fusion [9,10]. Compared with agematched controls, patients with POAG have been found to lose a greater number of TM cells as they age [11,12]. Moreover, it has been suggested that the absence of TM cells, followed by their replacement with extracellular matrix (ECM) leads to increased resistance to fluid outflow in these patients, thus triggering an increase in IOP [13].…”
Section: Introduction: Aging and Glaucoma Are Intimately Linkedmentioning
confidence: 99%